Effects of Constant Flow vs. Constant Pressure Perfusion on Fluid Filtration in Severe Hypothermic Isolated Blood-Perfused Rat Lungs - Halsøy, Kathrine; Kondratiev, Timofey; Tveita, Torkjel; Bjertnaes, Lars J. (Frontiers in Medicine, 2016)
Background: Victims of severe accidental hypothermia are prone to fluid extravasation, but rarely develop lung edema. We hypothesize that combined hypothermia-induced increase in pulmonary vascular resistance (PVR) and a concomitant fall in cardiac output protect the lungs against edema development. Our aim was to explore in hypothermic isolated blood perfused rat lungs whether perfusion at constant pressure influences fluid filtration differently from perfusion at constant flow. Methods: Isolated blood-perfused rat lungs were hanging freely in a weight transducer for measuring weight changes (∆W). Fluid filtration coefficient, (Kfc), was determined by transiently elevating left atrial pressure (Pla) by 5.8 mmHg two times each during normothermia (37 oC) and during hypothermia (15 oC). The lung preparations were randomized to two groups. One group was perfused with constant flow (Constant flow group) and the other group with constant pulmonary artery pressure (Constant PPA group). Microvascular pressure (Pmv) was determined before and during elevation of Pla (ΔPmv) by means of the double occlusion technique. Kfc was calculated with the formula Kfc = ∆W/∆Pmv/min. All Kfc values were normalized to predicted lung weight (PLW), which was based on body weight (BW) according to the formula: PLW = 0.0053·BW - 0.48 and presented as KfcPLW in mg/minute/mmHg/g. At cessation, bronchoalveolar lavage fluid (BAL)/perfusate protein concentration (B/P) ratio was determined photometrically. Data were analyzed with parametric or nonparametric tests as appropriate. p<0.05 considered as significant. Results: Perfusate flow remained constant in the Constant flow group, but was more than halved during hypothermia in the Constant PPA group concomitant with a more fold increase in PVR. In the Constant flow group, KfcPLW and B/P ratio increased significantly by more than ten-fold during hypothermia concerted by visible signs of edema in the trachea. Hemoglobin and hematocrit increased within the Constant flow group and between the groups at cessation of the experiments. Conclusion: In hypothermic rat lungs perfused at constant flow, fluid filtration coefficient per g predicted lung weight and B/P ratio increased more than 10-fold concerted by increased hemoconcentration, but the changes were less in hypothermic lungs perfused at constant PPA.